Indirubin-3'-oxime impairs mitochondrial oxidative phosphorylation and prevents mitochondrial permeability transition induction - Varela, Ana T. (2008)
http://www.sciencedirect.com/science/article/B6WXH-4T7085D-2/2/535e45a8cc0ac06fe24206561a5ee793